Questions to the external image of the Republic of China in the XXI century. - Amirgaliyeva., A. M. (Journal of Oriental Studies, 2016)
This article discusses aspects of the «internal» and «external» image of modern China. «Factor image» held an important role in the making of China as a major subject of the international relations.